The Influence of Occupational Health and Safety Practices on Employee Wellbeing in Uganda's Health Facilities: A Case Study of St. Mauritz Health Centre Iii, Obiya Palaro, Gulu City - Arthur Ronald Apire (Uganda Christian University, 2026)
This study examined the influence of Occupational Health and Safety (OHS) practices on employee wellbeing at St. Mauritz Health Centre III in Gulu District, Uganda. The study focused on health and safety training and the implementation of health and safety policies and their impact on the physical and psychological health of employees. The study followed the Job Demands-Resources Model in explaining the relationship that exists between workplace resources and stress. The study adopted a mixed-methods approach in a cross-sectional study. The study collected quantitative data from health workers through the use of questionnaires. The study also collected qualitative data from health workers. The study analyzed the quantitative data through descriptive statistics. The study also analyzed the qualitative data through thematic analysis. The study found that health and safety training had a positive impact on physical health. The study found that health and safety training helped to enhance employees' physical health through increased awareness of health and safety hazards and prevention of infections. However, the study also found some gaps that existed in health and safety training. The study found that occupational health and safety policies had a positive impact on employees' psychological health. The study found that effective implementation of occupational health and safety policies helped to enhance employees' psychological health. However, the study also found some gaps that existed in the implementation of occupational health and safety policies. The study concluded that occupational health and safety practices had a positive impact on employees' physical and psychological health. However, the study also found that occupational health and safety practices are effective when there is a focus on training and on physical and psychosocial health.
Undergraduate